Carbon Taxation, Prices and Welfare in New Zealand - John Creedy; Catherine Sleeman (New Zealand Government, The Treasury, 2004)
This paper examines the effects on consumer prices of a range of carbon taxes in New Zealand, using information about inter-industry transactions and the use of fossil fuels by industries. The resulting effects on the welfare of different household types and total expenditure levels are examined. The excess burdens of the carbon tax are computed for the different household types. Finally, overall measures of inequality are reported.
Keywords: H23; H31; D57; 330; Carbon tax; equivalent variations; excess burdens; inequality